Chain Rule Differentiation


In differential calculus, the chain rule is a formula for determining the derivative of the combined two or more functions. the chain rule could be used in Leibniz’s notation in the following way.
If $y=g(u)$ where $u=f(x)$ then $\displaystyle \dfrac{dy}{dx}=\dfrac{dy}{du} \times \dfrac{du}{dx}$.
Generally, the chain rule is described as following in its simplest understanding.
If $y=\big[f(x)\big]^n$ then $\displaystyle \dfrac{dy}{dx}=n\big[f(x)\big]^{n-1}\times f'(x)$.

Example 1

Find $\displaystyle \dfrac{dy}{dx}$ of $y=(x^2-4x)^5$.

\( \begin{align} \displaystyle
\dfrac{dy}{dx} &= 5(x^2-4x)^{5-1} \times \dfrac{d}{dx}(x^2-4x) \\
&= 5(x^2-4x)^4 (2x-4) \\
&= 10(x^2-4x)^4 (x-2) \\
\end{align} \)

Example 2

Find $\displaystyle \dfrac{dy}{dx}$ of $y=\dfrac{1}{(x^3-3)^6}$.

\( \begin{align} \displaystyle
\dfrac{1}{(x^3-3)^6} &= (x^3-3)^{-6} \\
\dfrac{dy}{dx} &= -6(x^3-3)^{-6-1} \times \dfrac{d}{dx}(x^3-3) \\
&= -6(x^3-3)^{-7} \times 3x^2 \\
&= \dfrac{-18x^2}{(x^3-3)^7} \\
\end{align} \)

Example 3

Find $\displaystyle \dfrac{dy}{dx}$ of $y=\sqrt{3x-1}$.

\( \begin{align} \displaystyle
\sqrt{3x-1} &= (3x-1)^{\frac{1}{2}} \\
\dfrac{dy}{dx} &= \dfrac{1}{2} (3x-1)^{\frac{1}{2}-1} \times \dfrac{d}{dx}(3x-1) \\
&= \dfrac{1}{2} (3x-1)^{-\frac{1}{2}} \times 3 \\
&= \dfrac{3}{2\sqrt{3x-1}} \\
\end{align} \)

Example 4

Find $\displaystyle \dfrac{dy}{dx}$ of $y=\sqrt[3]{x^2-x}$.

\( \begin{align} \displaystyle
\sqrt[3]{x^2-x} &= (x^2-x)^{\frac{1}{3}} \\
\dfrac{dy}{dx} &= \dfrac{1}{3}(x^2-x)^{\frac{1}{3}-1} \times \dfrac{d}{dx}(x^2-x) \\
&= \dfrac{1}{3}(x^2-x)^{-\frac{2}{3}} \times (2x-1) \\
&= \dfrac{2x-1}{3\sqrt[3]{(x^2-x)^2}} \\
\end{align} \)

Example 5

Find $\displaystyle \dfrac{dy}{dx}$ of $y=\dfrac{1}{\sqrt{x^3-2x}}$.

\( \begin{align} \displaystyle
\dfrac{1}{\sqrt{x^3-2x}} &= (x^3-2x)^{-\frac{1}{2}} \\
\dfrac{dy}{dx} &= -\dfrac{1}{2}(x^3-2x)^{-\frac{1}{2}-1} \times (x^3-2x) \\
&= -\dfrac{1}{2}(x^3-2x)^{-\frac{3}{2}} \times (3x^2-2) \\
&= -\dfrac{3x^2-2}{2\sqrt{(x^3-2x)^3}} \\
\end{align} \)

Extension Examples

These Extension Examples require to have some prerequisite skills including;
\( \begin{align} \displaystyle
\dfrac{d}{dx}\sin{x} &= \cos{x} \\
\dfrac{d}{dx}\cos{x} &= -\sin{x} \\
\dfrac{d}{dx}e^x &= e^x \\
\dfrac{d}{dx}\log_e{x} &= \dfrac{1}{x} \\
\end{align} \)

Example 6

Find $\displaystyle \dfrac{dy}{dx}$ of $y=\sin^3{x}$, known that $\dfrac{d}{dx}\sin{x} = \cos{x}$.

\( \begin{align} \displaystyle
y &= (\sin{x})^3 \\
\dfrac{dy}{dx} &= 3(\sin{x})^{3-1} \times \dfrac{d}{dx}\sin{x} \\
&= 3(\sin{x})^{2} \times \cos{x} \\
&= 3\sin^2{x}\cos{x} \\
\end{align} \)

Example 7

Find $\displaystyle \dfrac{dy}{dx}$ of $y=\cos^3{x}$, known that $\dfrac{d}{dx}\cos{x} = -\sin{x}$.

\( \begin{align} \displaystyle
y &= (\cos{x})^3 \\
\dfrac{dy}{dx} &= 3(\cos{x})^{3-1} \times \dfrac{d}{dx}\cos{x} \\
&= 3(\cos{x})^{2} \times (-\sin{x}) \\
&= -3\cos^2{x}\sin{x} \\
\end{align} \)

Example 8

Find $\displaystyle \dfrac{dy}{dx}$ of $y=e^{\sin{x}}$, known that $\dfrac{d}{dx}\sin{x} = \cos{x}$ and $\dfrac{d}{dx}e^x = e^x$.

\( \begin{align} \displaystyle
\dfrac{dy}{dx} &= e^{\sin{x}} \times \dfrac{d}{dx}\sin{x} \\
&= e^{\sin{x}}\cos{x} \\
\end{align} \)

Example 9

Find $\displaystyle \dfrac{dy}{dx}$ of $y=\sin{e^{2x}}$, known that $\dfrac{d}{dx}\sin{x} = \cos{x}$ and $\dfrac{d}{dx}e^x = e^x$.

\( \begin{align} \displaystyle
\dfrac{dy}{dx} &= e^{\sin{e^{2x}}} \times \dfrac{d}{dx}e^{2x} \\
&= e^{\sin{e^{2x}}} \times e^{2x} \times \dfrac{d}{dx}2x \\
&= e^{\sin{e^{2x}}} \times e^{2x} \times 2 \\
&= 2e^{\sin{e^{2x}}} e^{2x} \\
\end{align} \)

Example 10

Find $\displaystyle \dfrac{dy}{dx}$ of $y=\log_e{\sin{e^{x^2}}}$, known that $\dfrac{d}{dx}\sin{x} = \cos{x}$ and $\dfrac{d}{dx}\log_e{x} = \dfrac{1}{x}$.

\( \begin{align} \displaystyle
\dfrac{d}{dx} &= \dfrac{1}{\sin{e^{x^2}}} \times \dfrac{d}{dx}\sin{e^{x^2}} \\
&= \dfrac{1}{\sin{e^{x^2}}} \times \cos{e^{x^2}} \times \dfrac{d}{dx} e^{x^2} \\
&= \dfrac{1}{\sin{e^{x^2}}} \times \cos{e^{x^2}} \times e^{x^2} \times \dfrac{d}{dx}x^2 \\
&= \dfrac{1}{\sin{e^{x^2}}} \times \cos{e^{x^2}} \times e^{x^2} \times 2x \\
&= \dfrac{2xe^{x^2}\cos{e^{x^2}}}{\sin{e^{x^2}}} \\
\end{align} \)


Algebra Algebraic Fractions Arc Binomial Expansion Capacity Chain Rule Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorials Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Proof Pythagoras Theorem Quadratic Quadratic Factorise Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Your email address will not be published.